2008
DOI: 10.1111/j.1365-246x.2008.03863.x
|View full text |Cite
|
Sign up to set email alerts
|

Radial profiles of seismic attenuation in the upper mantle based on physical models

Abstract: Thermally activated, viscoelastic relaxation of the Earth's materials is responsible for intrinsic attenuation of seismic waves. Seismic observations have been used to define layered radially symmetric attenuation models, independent of any constraints on temperature and composition. Here, we interpret free-oscillation and surface wave attenuation measurements in terms of physical structures, by using the available knowledge on the physical mechanisms that govern attenuation at upper-mantle (<400 km) condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 73 publications
(124 reference statements)
1
16
1
Order By: Relevance
“…Attenuation is defined by the quality factor Q ¼ 2pE/DE, or its inverse Q -1 , where DE represents the loss of seismic energy per unit cycle and E denotes the elastic energy stored in the system. Estimated values of Q, for the crust and upper mantle, range between the lowest values of~30-40 for Q S (S-wave attenuation) in the asthenosphere to values of several thousands in lowattenuation regions (e.g., Cammarano and Romanowicz 2008). 5.…”
Section: Variations Of Seismic Properties As a Function Of Fluid Contmentioning
confidence: 99%
“…Attenuation is defined by the quality factor Q ¼ 2pE/DE, or its inverse Q -1 , where DE represents the loss of seismic energy per unit cycle and E denotes the elastic energy stored in the system. Estimated values of Q, for the crust and upper mantle, range between the lowest values of~30-40 for Q S (S-wave attenuation) in the asthenosphere to values of several thousands in lowattenuation regions (e.g., Cammarano and Romanowicz 2008). 5.…”
Section: Variations Of Seismic Properties As a Function Of Fluid Contmentioning
confidence: 99%
“…Much of the attenuation observed in seismic waves is caused by the thermally activated viscoelastic relaxation of the mineral aggregates within the Earth. The importance of attenuation effects in inversions of seismic data for the thermal and compositional structure of the upper mantle is well known [e.g., Afonso et al , 2010; Cammarano and Romanowicz , 2008; Goes et al , 2000; Sobolev et al , 1996]. Our understanding of viscoelastic relaxation at seismic frequencies (10–10 −4 Hz) in upper mantle mineral aggregates or analogues, and the relation between attenuation and grain size, have improved considerably in recent years thanks to new laboratory studies [e.g., Jackson and Faul , 2010; McCarthy et al , 2011].…”
Section: Inversion For Baikal–central Mongolia's Lithospheric Structurementioning
confidence: 99%
“…A short review of uncertainties in anelastic properties can be found in Cammarano & Romanowicz (2008). A more extended review, also illustrating the principles of the physical mechanisms responsible for attenuation, is given by Jackson (2008).…”
Section: The Mineral Physics Modelmentioning
confidence: 99%
“…Alternatively, an unrealistically strong negative thermal gradient with depth would need to be invoked. The purely thermal explanation is not only unphysical, as discussed in Cammarano & Romanowicz (2007), but it would imply intrinsic values of Q S (shear quality factor) that are too high compared to the values compatible with global observations of seismic attenuation (see Cammarano & Romanowicz 2008). We also speculated that a purely compositional explanation would be consistent with an upper mantle that is not chemically equilibrated, but contains 3‐D compositional heterogeneity at a scale beyond the resolution of the long‐period data used in that study.…”
Section: Introductionmentioning
confidence: 99%